IMPLEMENTASI MEDIA AUDIO-VISUAL TERHADAP KEMAMPUAN MEMBACA PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Lutvia, Halimatul; Ainul Yaqin, Firdaus; Purwantoro, Farich (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low reading ability of first-grade students at Tarbiyatul Islam Elementary School, especially in the aspects of letter recognition, pronunciation, reading fluency, and comprehension of simple reading content. This problem is influenced by students' low interest in reading, differences in individual abilities, and the use of conventional learning methods and the lack of utilization of interesting learning media. This condition causes students to be less active and less motivated in participating in reading lessons. Therefore, innovation is needed in the learning process, one of which is through the use of audio-visual media that can combine sound and image elements simultaneously. This study aims to describe the implementation of audio-visual media in reading learning and to determine students' reading abilities after the implementation of the media. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions, and data validity is tested through triangulation. The results show that the implementation of audio-visual media is carried out through the stages of planning, implementation, and evaluation of learning. The use of audio-visual media can increase students' interest, attention, and motivation to learn. Furthermore, students' reading skills improve, as evidenced by increased reading fluency, pronunciation accuracy, appropriate intonation, and increased comprehension of the reading content. Therefore, audio-visual media is an effective alternative learning tool for improving students' reading skills in Islamic elementary schools.